Cre driver mouse lines for thalamocortical circuit mapping. Issue 7 (20th October 2021) - Sokhadze, Guela; Campbell, Peter W.; Charalambakis, Naomi; Govindaiah, Gubbi; Guido, William; McGee, Aaron W.
Abstract: Subpopulations of neurons and associated neural circuits can be targeted in mice with genetic tools in a highly selective manner for visualization and manipulation. However, there are not well‐defined Cre "driver" lines that target the expression of Cre recombinase to thalamocortical (TC) neurons. Here, we characterize three Cre driver lines for the nuclei of the dorsal thalamus: Oligodendrocyte transcription factor 3 ( Olig3)‐Cre, histidine decarboxylase (HDC)‐Cre, and corticotropin‐releasing hormone ( CRH)‐Cre . We examined the postnatal distribution of Cre expression for each of these lines with the Cre‐dependent reporter CAG‐tdTomato ( Ai9) . Cre‐dependent expression of tdTomato reveals that Olig3‐Cre expresses broadly within the thalamus, including TC neurons and interneurons, while HDC‐Cre and CRH‐Cre each have unique patterns of expression restricted to TC neurons within and across the sensory relay nuclei of the dorsal thalamus. Cre expression is present by the time of natural birth in all three lines, underscoring their utility for developmental studies. To demonstrate the utility of these Cre drivers for studying sensory TC circuitry, we targeted the expression of channelrhodopsin‐2 to thalamus from the CAG‐COP4*H134R/EYFP (Ai32) allele with either HDC‐Cre or CRH‐Cre . Optogenetic activation of TC afferents in primary visual cortex was sufficient to measure frequency‐dependent depression. Thus, these Cre drivers provide selective Cre‐dependent gene expression in thalamus suitable for both anatomical and functional studies. Abstract : This study characterizes the temporal and spatial expression pattern of genetically encoded reporters following Cre‐mediated recombination from three Cre drivers selective for the nuclei of the dorsal thalamus: Oligodendrocyte transcription factor 3 ( Olig3)‐Cre, histidine decarboxylase (HDC)‐Cre, and corticotropin‐releasing hormone ( CRH)‐Cre . Cre‐dependent expression of tdTomato reveals that Olig3‐Cre expresses broadly within the thalamus, including thalamocortical (TC) neurons and interneurons, while HDC‐Cre and CRH‐Cre each have unique patterns of expression restricted to TC neurons within and across the sensory relay nuclei of the dorsal thalamus.